2018
DOI: 10.1001/jamadermatol.2017.6428
|View full text |Cite
|
Sign up to set email alerts
|

Validating 4 Staging Systems for Cutaneous Squamous Cell Carcinoma Using Population-Based Data

Abstract: IMPORTANCE Cutaneous squamous cell carcinoma (cSCC) has metastatic potential, but the prognostic value of current staging systems in nonselected patients is uncertain. OBJECTIVE To assess the effect of risk factors for metastasis and to evaluate validity and usefulness of 4 staging systems for cSCC using population-based data. DESIGN, SETTING, AND PARTICIPANTS This was a nationwide, population-based, nested case-control study. The Cancer Registry of Norway, which receives compulsory data on all cancers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
81
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 31 publications
(90 reference statements)
5
81
0
1
Order By: Relevance
“…Staging systems (AJCC 7th and 8th version, BWH and Breuninger) were compared in a population-based cohort study where the BWH and Breuninger systems performed best in identifying cSCC patients at high risk of metastases [115]. However it was commented that staging systems were still not optimal [116].…”
Section: Prognostic Factors For High-risk Csccmentioning
confidence: 99%
See 1 more Smart Citation
“…Staging systems (AJCC 7th and 8th version, BWH and Breuninger) were compared in a population-based cohort study where the BWH and Breuninger systems performed best in identifying cSCC patients at high risk of metastases [115]. However it was commented that staging systems were still not optimal [116].…”
Section: Prognostic Factors For High-risk Csccmentioning
confidence: 99%
“…However it was commented that staging systems were still not optimal [116]. Among the 103 patients with metastasis, 37.9% fell in the BWH T2a and 39.8% in BWH T2b category, while with AJCC8 more than 60% fell in the T3 category [115]. AJCC8 was compared with the BWH classification system in the retrospective study of Ruiz et al in 680 primary CSCC of the head and neck.…”
Section: Prognostic Factors For High-risk Csccmentioning
confidence: 99%
“…The clinical risk factors for cSCC recurrence include tumor invasion depth, size, differentiation status, presence of perineural invasion and location (6). In addition, certain molecular biomarkers, including tumor protein 53, cyclin-dependent kinase inhibitor 2A, telomerase reverse transcriptase gene (TERT) and programmed cell death ligand 1 (PD-L1) have been considered as potential factors involved in cSCC progression.…”
Section: Axin2 and Snail Expression Predict The Risk Of Recurrence Inmentioning
confidence: 99%
“…In particular, TERT promoter mutations and increased PD-L1 expression have been considered as molecular risk factors for cSCC recurrence (7)(8)(9). However, these predictive risk factors are inadequate to properly assess the recurrence risk of cSCC with high reproducibility and reliability (5,6).…”
Section: Axin2 and Snail Expression Predict The Risk Of Recurrence Inmentioning
confidence: 99%
“…6 Roscher et al directly compared multiple staging systems (AJCC 7, AJCC 8, BWH, Breuninger) for cSCC using a population-based, nested case-control study and showed AJCC 8 and BWH systems performed better than AJCC 7. 9 A formal staging system for BCC does not exist. Historically, it has been grouped together with other cutaneous malignancies, including cSCC, in the AJCC.…”
mentioning
confidence: 99%